2015
DOI: 10.1002/ps.4155
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive overexpression of cytochrome P450 associated with imidacloprid resistance in Laodelphax striatellus (Fallén)

Abstract: Constitutive overexpression of four CYP genes was associated with imidacloprid resistance in long-term selection, and expression of CYP353D1v2 with imidacloprid resistance in short-term selection in L. striatellus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 34 publications
1
69
0
Order By: Relevance
“…In this study, the expression level of CYP3356A1 was significantly induced by imidacloprid, thiamethoxam, and β‐cypermethrin, although no statistical difference was found after chlorpyrifos exposure. It is reported that the enhanced transcript level of CYP353D1v2 was correlated with imidacloprid resistance in Laodelphax striatellus . Overexpression of detoxification‐related P450 was related to thiamethoxam resistance in Aphis gossypii Glover .…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the expression level of CYP3356A1 was significantly induced by imidacloprid, thiamethoxam, and β‐cypermethrin, although no statistical difference was found after chlorpyrifos exposure. It is reported that the enhanced transcript level of CYP353D1v2 was correlated with imidacloprid resistance in Laodelphax striatellus . Overexpression of detoxification‐related P450 was related to thiamethoxam resistance in Aphis gossypii Glover .…”
Section: Discussionmentioning
confidence: 98%
“…For instance, through RNAi studies, several studies have shown that constitutive upregulation of CYPs mediates resistance to pyrethroid insecticides in the diamondback moth, Plutella xylostella 35 , the carmine spider mite, Tetranychus cinnabarinus 36 , and the red flour beetle, Tribolium castaneum 37 . Additionally, CYPs are involved in resistance to neonicotinoids in the small brown plant hopper, Laodelphax striatellus 38 and the tobacco whitefly, B. tabaci 39 , to organophosphates in the tobacco cutworm, Spodoptera litura 40 , and to abamectin in P . xylostella 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, multiple overexpressed P450 genes are responsible for high levels of insecticide by resistance in insects, such as the co‐upregulation of multiple P450 genes in permethrin‐resistant house flies (Zhu et al ., ) and Culex mosquitoes (Liu et al ., ; Yang & Liu, ). Here, CYP6AY3v2 was also co‐upregulated with CYP4C71v2 , CYP4C72 and CYP353D1v2 in the L. striatellus imidacloprid‐resistant strain Imid‐R (Elzaki et al ., ). CYP4C71v2 was reactive against imidacloprid, as there was apparent substrate depletion observed in in vitro metabolism assays (unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…() indicated that piperonyl butoxide had significant synergistic effects on three imidacloprid‐resistant L. striatellus populations. A previous study by our laboratory also showed that the expression level of a cytochrome P450 gene CYP6AY3v2 was significantly upregulated in a L. striatellus imidacloprid‐resistant strain (Imid‐R; Elzaki et al ., ). In this study, a transgenic Drosophila melanogaster line that overexpressed the L. striatellus CYP6AY3v2 gene was established to validate metabolism‐based imidacloprid resistance, and CYP6AY3v2 was functionally expressed in Spodoptera frugiperda 9 (SF9) cells to examine its metabolizing ability of imidacloprid.…”
Section: Introductionmentioning
confidence: 97%